Self-Assembly-Induced Alternately Stacked Single-Layer MoS2 and N-doped Graphene: A Novel van der Waals Heterostructure for Lithium-Ion Batteries - Zhao, Chenyang (2017)
In this article, a simple self-assembly strategy for fabricating van der Waals heterostructures from isolated two-dimensional atomic crystals is presented. Specifically, dopamine (DOPA), an excellent self-assembly agent and carbon precursor, was adsorbed on exfoliated MoS2 monolayers through electrostatic interaction, and the surface-modified monolayers self-assembled spontaneously into DOPA-intercalated MoS2. The subsequent in situ conversion of DOPA to highly conductive nitrogen-doped graphene (NDG) in the interlayer space of MoS2 led to the formation of a novel NDG/MoS2 nanocomposite with well-defined alternating structure. The NDG/MoS2 was then studied as an anode for lithium-ion batteries (LIBs). The results show that alternating arrangement of NDG and MoS2 triggers synergistic effect between the two components. The kinetics and cycle life of the anode are greatly improved due to the enhanced electron and Li+ transport as well as the effective immobilization of soluble polysulfide by NDG. A reversible capacity of more than 460 mAh/g could be delivered even at 5 A/g. Moreover, the abundant voids created at the MoS2–NDG interface also accommodate the volume change during cycling and provide additional active sites for Li+ storage. These endow the NDG/MoS2 heterostructure with low charge-transfer resistance, high sulfur reservation, and structural robustness, rendering it an advanced anode material for LIBs.